An Application of the "Fan-Chart Approach" to Debt Sustainability in Post-HIPC Low-Income Countries - Kaffo Melou, Maximilien; Geiregat, Chris; Sumlinski, Mariusz (Washington, D.C. : International Monetary Fund, 2014)
We analyse the debt dynamics in countries that benefited from the HIPC/MDRI debt relief initiatives with a view to applying a probabilistic approach to estimating future debt paths for those countries. We extend the probabilistic approach to public debt sustainability analysis (DSA) proposed by Celasun and others (2006). This required addressing the twin challenges of a the time period that is too short to conduct country-by-country estimations and the presence, suggested by econometric evidence, of a break-point around 2006 in the dynamics of debt accumulation. To overcome the data limitations, we pool the data and estimate a panel VAR, thus taking advantage of the large cross-section. To account for the break-point, while applying a probabilistic approach to forecasting debt paths, we use the post-break-point information so as not to bias the forecasts of debt paths. As an illustration of the approach we apply the methodology to eight countries with different debt profiles.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet